Digital Literature Based on Gender Equality (Study on Cyberfeminist Phenomenology at The Department of Social Sciences FITK IAIN Syekh Nurjati Cirebon) - Ratna Puspitasari; Septiani Resmalasari; Musyarofah Musyarofah (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
In this millennial era of the 21st century, the demands for skills to become students so that they master a variety of skills that are very relevant to the four pillars of life, including learning to know, learning to do, learning to be, and learning to live together, each of which contains aspects of important special skills, Activated in the learning process including critical thinking skills, problem-solving, communication skills, collaboration skills, metacognition, innovation and creation, literacy and various other skills. Improving the quality of learning supports participants in developing participation, adjusting learning personalization, prioritizing the PJBL learning model, encouraging collaboration and communication aspects, increasing student involvement and motivation, cultivating creativity and learning innovation, using appropriate learning tools, designing relevant learning activities with everyday life and the development of student center learning. One aspect of these skills is digital literacy. Digital literacy is essential to gender equality issues, especially for students in the PTKIN environment. The author examines Barry's Theory, 2012, in describing three dimensions of 21st-century learning consisting of information, communication, and ethics, as well as the social influence of gender equality aspects. The author uses qualitative research with a phenomenological approach in the Gender Equality Study lecture at the TIPS FITK Department of IAIN Syekh Nurjati Cirebon. Cyber ​​feminists in social studies learning have a role that is exceptionally influential on Tadris IPS students from activities that take place online, including fighting for equal rights between women and men in all aspects, actively synergizing.